2019
DOI: 10.5603/gp.2019.0036
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dexamethasone plus acetylsalicylic acid treatment during in vitro fertilization procedure

Abstract: Objectives: Embryo implantation represents the major limiting step during in vitro fertilization (IVF) procedure. Immunological and coagulation abnormalities were shown to have a substantial part in multifactorial etiology of IVF failure. We aimed to investigate the effect of short-term low-dose dexamethasone plus acetylsalicylic acid (ASA) treatment, starting at the time of embryo transfer, on the implantation and clinical pregnancy rates in general IVF population. Material and methods:Out of 233 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In our study, treatment started on the day of embryo transfer and lasted for 2-6weeks, mainly focusing on improving the implantation micro-immune environment. In a prospective case-control study including 233 consecutive patients, dexamethasone (0.5 mg/d) and acetylsalicylic acid (100 mg/d) starting from the day of embryo transfer and until the end of the 12th week of gestation increased the PR and implantation rate when compared with the control group [40]. Nevertheless, the inclusion criteria of this prospective study included inherited and acquired thrombophilia, compound heterozygous polymorphisms, positive anti-nuclear and anti-thyroglobulin antibodies, which were the strong indication for steroid hormone and anticoagulant drug [40].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, treatment started on the day of embryo transfer and lasted for 2-6weeks, mainly focusing on improving the implantation micro-immune environment. In a prospective case-control study including 233 consecutive patients, dexamethasone (0.5 mg/d) and acetylsalicylic acid (100 mg/d) starting from the day of embryo transfer and until the end of the 12th week of gestation increased the PR and implantation rate when compared with the control group [40]. Nevertheless, the inclusion criteria of this prospective study included inherited and acquired thrombophilia, compound heterozygous polymorphisms, positive anti-nuclear and anti-thyroglobulin antibodies, which were the strong indication for steroid hormone and anticoagulant drug [40].…”
Section: Discussionmentioning
confidence: 97%
“…In a prospective case-control study including 233 consecutive patients, dexamethasone (0.5 mg/d) and acetylsalicylic acid (100 mg/d) starting from the day of embryo transfer and until the end of the 12th week of gestation increased the PR and implantation rate when compared with the control group [40]. Nevertheless, the inclusion criteria of this prospective study included inherited and acquired thrombophilia, compound heterozygous polymorphisms, positive anti-nuclear and anti-thyroglobulin antibodies, which were the strong indication for steroid hormone and anticoagulant drug [40]. Coincidentally, its inclusion criteria coincided with the exclusion criteria in our study, which largely explained the con icting results.…”
Section: Discussionmentioning
confidence: 97%
“…Such a medication approach was acknowledged as of value on pregnancy and implantation rates in contrast with untreated ATA + patients [34].The timing of medication in our study commenced on the day of embryo transfer and lasted for 2-6weeks, mainly focusing on fascinating the implantation micro-immune environment. In a prospective casecontrol study including 233 consecutive patients, dexamethasone(0.5 mg/d) and acetylsalicylic acid(100 mg/d) starting from the day of embryo transfer and continuing until the end of the 12th week of gestation increased the pregnancy rate and implantation rate when compared with the control group [42].But it was noteworthy that the inclusion of this prospective study was inherited and acquired thrombophilia, compound heterozygous polymorphisms, positive anti-nuclear and anti-thyroglobulin antibodies, the strong indication for steroid hormone and anticoagulant drug [42]. Coincidentally, its inclusion standard was exactly in line with the exclusion criteria in our study, which largely explained the con icting results.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, treatment started on the day of embryo transfer and lasted for 2–6 weeks, mainly focusing on improving the micro-immune environment of the implantation site. In a prospective case-control study including 233 consecutive patients, dexamethasone (0.5 mg/d) and acetylsalicylic acid (100 mg/d) starting from the day of embryo transfer and until the end of the 12th week of gestation increased the pregnancy rate and implantation rate when compared with the control group [ 19 ]. The inclusion criteria of this prospective study included inherited and acquired thrombophilia, compound heterozygous polymorphisms, and positive anti-nuclear and anti-thyroglobulin antibodies, which were strong indications for steroid hormone and anticoagulant drugs [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a therapeutic alternative, corticosteroid hormones in combination with aspirin may potentially benefit blood perfusion to the ovaries and endometrium and decrease local inflammatory reactions to the transfer procedure, thereby inducing a more favorable microenvironment for the transferred embryo [ 14 , 15 ]. Furthermore, previous investigations have indicated that combined treatment of P + A is effective for women with various autoimmune diseases [ 16 19 ]. However, these trials were published long ago and do not demonstrate the efficacy of this approach in infertile women who are positive only for antithyroid antibodies.…”
Section: Introductionmentioning
confidence: 99%